(3MeGSI CHj JeGes - (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s
(3ChdgG (B:s
(3PcQJc hGdNWi jNWQ HjffG hbO fgdJ YfG GdeKbaI GdSeQ s
(3BNQgG (B:s
(3Ydi fZGfZ SGdJ aj jdGYegG cKjQI GdhTi aj djf hJQajb cCfeG djSJ Ch CdHSJ afcG abdUJ MhGTjg Yf GdShb s
(3fSNI SGOSIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B170s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B272 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B691s
Keywords: (3GdCOHs